Π‐Hole Interactions Involving Nitro Aromatic Ligands in Protein Structures. Issue 58 (17th September 2019) - Bauzá, Antonio; Frontera, Antonio; Mooibroek, Tiddo Jonathan
Abstract: Studying noncanonical intermolecular interactions between a ligand and a protein constitutes an emerging research field. Identifying synthetically accessible molecular fragments that can engage in intermolecular interactions is a key objective in this area. Here, it is shown that so‐called "π‐hole interactions" are present between the nitro moiety in nitro aromatic ligands and lone pairs within protein structures (water and protein carbonyls and sulfurs). Ample structural evidence was found in a PDB analysis and computations reveal interaction energies of about −5 kcal mol −1 for ligand–protein π‐hole interactions. Several examples are highlighted for which a π‐hole interaction is implicated in the superior binding affinity or inhibition of a nitro aromatic ligand versus a similar non‐nitro analogue. The discovery that π‐hole interactions with nitro aromatics are significant within protein structures parallels the finding that halogen bonds are biologically relevant. This has implications for the interpretation of ligand–protein complexation phenomena, for example, involving the more than 50 approved drugs that contain a nitro aromatic moiety. Abstract : Nitro aromatic ligands have a positive electrostatic potential on the nitro group N atom (the so‐called π‐hole) that can interact with lone‐pair O/S electrons with energies of about −5 kcal mol −1 . A thorough Protein Data Bank (PDB) analysis and scrutiny of relevant literature revealed the structural and functional significance of π–hole interactions of nitro aromatic ligands within proteins.